The plague: a case of delusional infestation with folie à deux - Sereijo, Ana Carolina de Melo Diogo (2022)
Folie à deux or Shared psychotic disorder (SPD) is a rare condition characterized by shared psychotic symptoms between two or more individuals. Delusional parasitosis (DP) is an uncommon psychiatric illness in that patients believe they are infested by insects, without evidence to support this belief. DP occurs in 5–15% of SPD. We report a case of cutaneous DP with SPD between an elderly mother and a daughter that lived together and withdrew from other social contacts for the last three years. We aim to highlight the relationship between SPD and DP, its prognosis, and clinical implications.